Cost-Effectiveness of Hypertension Treatment by Pharmacists in Black Barbershops. Issue 24 (15th April 2021) - Bryant, Kelsey B.; Moran, Andrew E.; Kazi, Dhruv S.; Zhang, Yiyi; Penko, Joanne; Ruiz-Negrón, Natalia; Coxson, Pamela; Blyler, Ciantel A.; Lynch, Kathleen; Cohen, Laura P.; Tajeu, Gabriel S.; Fontil, Valy; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In LABBPS (Los Angeles Barbershop Blood Pressure Study), pharmacist-led hypertension care in Los Angeles County Black-owned barbershops significantly improved blood pressure control in non-Hispanic Black men with uncontrolled hypertension at baseline. In this analysis, 10-year health outcomes and health care costs of 1 year of the LABBPS intervention versus control are projected. Methods: A discrete event simulation of hypertension care processes projected blood pressure, medication-related adverse events, fatal and nonfatal cardiovascular disease events, and noncardiovascular disease death in LABBPS participants. Program costs, total direct health care costs (2019 US dollars), and quality-adjusted life-years (QALYs) were estimated for the LABBPS intervention and control arms from a health care sector perspective over a 10-year horizon. Future costs and QALYs were discounted 3% annually. High and intermediate cost-effectiveness thresholds were defined as <50 000 and <150 000 per QALY gained, respectively. Results: At 10 years, the intervention was projected to cost an average of 2356 (95% uncertainty interval, –264 to 4611) more per participant than the control arm and gain 0.06 (95% uncertainty interval, 0.01–0.10) QALYs. The LABBPS intervention was highly cost-effective, with a mean cost of 42 717 per QALY gained (58% probability of being highly and 96% of being at least intermediately cost-effective). Exclusive use of generic drugs improved the cost-effectiveness to 17 162 per QALY gained. The LABBPS intervention would be only intermediately cost-effective if pharmacists were less likely to intensify antihypertensive medications when systolic blood pressure was ≥150 mm Hg or if pharmacist weekly time driving to barbershops increased. Conclusions: Hypertension care delivered by clinical pharmacists in Black barbershops is a highly cost-effective way to improve blood pressure control in Black men.